Experiences of stigma and health service utilization among young rural-to-urban migrants in China: the mediation role of social capital. Issue 2 (2nd April 2020) - Zeng, Chengbo; Li, Xiaoming; Du, Hongfei; Lin, Danhua
ABSTRACT: Previous studies revealed that experiences of stigma might negatively affect health service utilization (HSU) among young rural-to-urban migrants. Existing literature also suggested social factors including social capital might mediate such negative effect. However, data are limited regarding the mediation role of social capital among this vulnerable population. Therefore, the current study aimed to examine the associations among experiences of stigma, social capital, and HSU among young rural-to-urban migrants in China. A sample of 641 young rural-to-urban migrants was recruited through a venue-based sampling approach in Beijing, China. Participants were assessed on sociodemographic characteristics, experiences of stigma, and social capital in their urban communities. Self-reported frequency of physical examinations (regularly, irregularly, none) was used as an indicator of HSU. Structural equation modeling (SEM) was performed to examine the direct effect of stigma on HSU as well as the mediation effect of social capital. Among the 641 young rural-to-urban migrants, 32.3% (195/603) reported never having physical examinations while 50.6% (305/603) reported having them irregularly. The final model showed a goodness of fit ( χ 2 / df = 1.7, CFI = 0.98, RMSEA = 0.03, WRMR = 0.74). Results of SEM revealed that both of the direct and indirect paths from experiences of stigma on HSU were statistically significant. There was a partial mediation effect of social capital on the association between experiences of stigma and HSU (delta z score = −5.49, p < 0.01). Rural-to-urban migrants had a low rate of regular HSU. Experiences of stigma were associated with decreased likelihood of HSU. Social capital in the urban communities could mediate the negative effect of stigma on HSU and played a mediation role between experiences of stigma and HSU. Therefore, to increase HSU among migrants, targeted interventions to reduce stigma and increase social capital at the migration destinations are needed.